Global and regional shock transmission: An Asian perspective - Nagendra Shrestha; Kiyotaka Sato (Journal of Economic Structures, 2021)
This paper constructs and uses the global input-output (GIO) table with 35 industries, 29 endogenous countries and 59 exogenous countries, and develops new indices to measure the degree of shock transmission in terms of intermediate goods and value-added embodied in production induced by negative global demand shock to finished goods. After the Global Financial Crisis (GFC) in 2008, China did not experience a large decline in economic growth, even though China's gross exports fell most severely among Asian countries. In contrast, a sharp decrease in Japanese GDP in 2009 is a consequence of a substantial decline in finished goods exports, especially in the transport equipment industry. In Japan, the shock effect tends to be absorbed in its domestic sector and is not transmitted to other foreign countries. An asymmetric pattern of shock transmission between Japan and other Asian countries can explain why Japan was more affected by GFC than other Asian countries.
Keywords: F15; F33; F42; F44; 330; Asia; Global input-output table; Intermediate goods trade; Production-chain; Shock transmission; Value-added trade